Gestational complications associated with COVID-19 (Research, Society and Development, 2022)
Identify the main pregnancy complications associated with infection by COVID-19 in the literature. This is an integrative literature review that sought to analyze the review and identify the main pregnancy complications caused by COVID-19. The search was carried out in the Virtual Health Library (VHL), between the months of August and October 2021, using the databases of the Latin American and Caribbean Literature on Health Sciences (LILACS) and the Online Search and Analysis System of Medical Literature (MEDLINE). Table 1 shows the studies by title, author and year of publication, objectives and conclusions following the chronological order of publication. Pregnant women with COVID-19 may have atypical complications, initially without fever or just leukocytosis, but pneumonia has a similar evolution to non-pregnant women. In addition to the demonstrated gestational hypertension is 5 times more associated with women with COVID-19 infection compared to non-pregnancy, it was also clear that the risk of placental abruption is 21 times associated with infection. Newborns from mothers infected with the virus had a higher risk of admission to the NICU. Although initial studies show that there are no important differences in the frequency of COVID-19 between pregnant and non-pregnant women, the virus is responsible for important changes in pregnant women.